CONTRIBUTION OF STUDENTS’ WRITING INTEREST TOWARD THEIR WRITING SKILL OF PROCEDURE TEXT (A CORRELATIONAL RESEARCH AT GRADE IX STUDENTS OF SMP NEGERI 1 TEMPULING) - Tiara Hartantri; Samsul Amri; Syafrizal (Program Studi Pendidikan Bahasa Inggris, 2025)
The main objective of this study was to determine the contribution of the relationship between student interests and the ability to write procedural texts in grade IX students of SMP Negeri 1 Tempuling. This study is a correlation study and uses a random sample method and the number of samples is 52 people. Data collection using a questionnaire containing statements related to interests and tests for the ability to write procedural texts. The indicators assessed in the writing test, especially procedural texts, are content, text structure, vocabulary, grammar, and mechanics. From the results of the analysis of 52 students containing questions related to the correlation of interest indicators originating from within the students is 0.130 (very low) while the contribution value of the relationship between the two is 1.69%. To test the hypothesis, it can be calculated (0.130) is smaller than 0.279 indicating that Ho is accepted and Ha is rejected. Ho means there is no significant relationship between students' interest and the ability to write procedural texts in class IX students of SMP Negeri 1 Tempuling.